NF-κB-mediated developmental delay extends lifespan in Drosophila - Ping Kang; Peiduo Liu; Yanhui Hu; Jinoh Kim; Ankur Kumar; Marlene K. Dorneich-Hayes; Wren Murzyn; Zenessa J. Anderson; Lexi N. Frank; Nicholas Kavlock; Elizabeth Hoffman; Chad C. Martin; et al. (Proceedings of the National Academy of Sciences, 2025)
Developmental time (or time to maturity) strongly correlates with an animal’s maximum lifespan, with late-maturing individuals often living longer. However, the genetic mechanisms underlying this phenomenon remain largely unknown. This may be because most previously identified longevity genes regulate growth rate rather than developmental time. To address this gap, we genetically manipulated prothoracicotropic hormone (PTTH), the primary regulator of developmental timing in Drosophila , to explore the genetic link between developmental time and longevity. Loss of PTTH delays developmental timing without altering the growth rate. Intriguingly, PTTH mutants exhibit extended lifespan despite their larger body size. This lifespan extension depends on ecdysone signaling, as feeding 20-hydroxyecdysone to PTTH mutants reverses the effect. Mechanistically, loss of PTTH blunts age-dependent chronic inflammation, specifically in fly hepatocytes (oenocytes). Developmental transcriptomics reveal that NF-κB signaling activates during larva-to-adult transition, with PTTH inducing this signaling via ecdysone. Notably, time-restricted and oenocyte-specific silencing of Relish (an NF-κB homolog) at early 3rd instar larval stages significantly prolongs adult lifespan while delaying pupariation. Our study establishes an aging model that uncouples developmental time from growth rate, highlighting NF-κB signaling as a key developmental program in linking developmental time to adult lifespan.